Dental students’ reports of occupational exposures to potentially infectious biological material in a Brazilian School of Dentistry - Pinelli, Camila; Neri, Sabrina Do Nascimento; Loffredo, Leonor De Castro Monteiro (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2016)
AbstractIntroduction Occupational exposures to contaminated biological material in dental teaching settings can place students at higher risk of bloodborne infections.Methods This cross sectional study was conducted using a self-administered questionnaire culturally adapted to Portuguese language, Brazil. In total, 173 undergraduate dental students agreed to participate in the study, answered the questionnaire, and filled in the details about their own occupational exposures. The association of these factors was analyzed by the chi-square test or Fisher's exact test using Stata® software.Results High prevalence of occupational exposures (40%) was observed among the participants, and 52% of the accidents were not reported to the clinical instructor. The most frequent type of accident was related to “puncture/cut/abrasion” (56%). Significant correlation was observed between number of exposures and academic year (p=0.002), age (p=0.012), gender (p=0.010), and between number of injuries in the last 6 months and academic year (p=0.003). No significant correlation was observed between number of exposures and dominant hand, use of protective eyewear or Hepatitis B vaccination status (p>0.05).Conclusion Additional teaching strategies need to be developed to motivate adherence to occupational post-exposure protocols regarding biological material, improving the notification of the occupational exposures that occur among dental students.

ResumoIntrodução A exposição ocupacional a material biológico contaminado em ambientes de ensino de odontologia pode colocar os estudantes em maior risco de infecções transmissíveis pelo sangue.Métodos Tratou-se de um estudo transversal de avaliação, com questionário auto administrado e culturalmente adaptado para o português do Brasil. Ao total, 173 estudantes de odontologia concordaram em participar e forneceram detalhes sobre suas exposições ocupacionais. A associação de fatores foi analisada por meio do teste do qui-quadrado e/ou teste exato de Fisher, com auxílio do programa Stata®.Resultados Entre os participantes, houve alta prevalência a exposições ocupacionais (40%), e 52% dos acidentes não foram comunicados ao instrutor. O mais frequente ferimento foi do tipo “punção/ corte/ abrasão” (56%). Houve associação significativa entre “número de exposições” e “série” (p=0,002), “idade” (p=0,012) e “sexo” (p=0,010), e entre outras duas variáveis: “número de lesões nos últimos seis meses” e “série” (p=0,003). Não houve associação significativa entre o “número de exposições” e “mão dominante”, “uso de óculos de proteção” ou “estado vacinal contra o vírus da Hepatite B” (p>0,05).Conclusão Estratégias de ensino adicionais precisam ser implementadas para motivar a adesão aos protocolos pós-exposição ocupacional a material biológico, favorecendo a notificação dos casos entre acadêmicos de odontologia.
Estudantes de odontologia e o relato das exposições ocupacionais a material biológico potencialmente contaminado em uma Faculdade de Odontologia no Brasil
Keywords: occupational exposure; blood; body fluids; infection control; dental students; exposição ocupacional; sangue; fluidos corpóreos; biossegurança; estudantes de odontologia